1984
DOI: 10.1002/j.1460-2075.1984.tb02195.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the acidic compartment of Plasmodium falciparum-infected human erythrocytes as the target of the antimalarial drug chloroquine.

Abstract: Chloroquine (CQ), the most widely used antimalarial drug, is an acidotropic agent (De Duve, 1983) which accumulates to high levels in malaria-infected erythrocytes. A possible site of accumulation of the drug, the parasite's food vacuole, has been implicated in the mode of action of CQ. We have defined the various compartments of Plasmodium falciparumparasitized human erythrocytes in tenns of their pH and capacity to accumulate bases. The host cell and the parasite cytosols were differentially labeled in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
192
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(202 citation statements)
references
References 24 publications
7
192
1
1
Order By: Relevance
“…The location of this haem is not known, but as very little haem appears to escape the parasite (as judged by the total iron levels), much of the haem may be associated with membranes within the parasite. If even half of this amount of haem in located in the food vacuole, which represents less than 5 % of the total volume of the infected erythrocytes [30], a local haem concentration of a few millimolar could be reached. A concentration of haem in the millimolar range is sufficient to cause substantial membrane lysis and peroxidative damage, although the presence of specialized haem-binding proteins in the food vacuole environment may protect the food vacuole membrane from the lytic effects of the haem [31].…”
Section: Haem Undergoes Peroxidative Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of this haem is not known, but as very little haem appears to escape the parasite (as judged by the total iron levels), much of the haem may be associated with membranes within the parasite. If even half of this amount of haem in located in the food vacuole, which represents less than 5 % of the total volume of the infected erythrocytes [30], a local haem concentration of a few millimolar could be reached. A concentration of haem in the millimolar range is sufficient to cause substantial membrane lysis and peroxidative damage, although the presence of specialized haem-binding proteins in the food vacuole environment may protect the food vacuole membrane from the lytic effects of the haem [31].…”
Section: Haem Undergoes Peroxidative Decompositionmentioning
confidence: 99%
“…Chloroquine resistance is thought to arise, at least in part, from a decreased level of chloroquine uptake, although some studies suggest that an alteration in the drug target may also be involved [30,36,45]. Chloroquine resistance can be reversed in itro and in animal models by co-administration of compounds such as verapamil, chlorpromazine and desipramine [46][47][48].…”
Section: Resistance-modulating Agents Inhibit the Peroxidative Destrumentioning
confidence: 99%
“…Acidic compartments are organelles present in Plasmodium and several trypanosomatids (Docampo & Moreno 2001). For Plasmodium, it has been suggested that these organelles are the food vacuole in which hemoglobin is digested and antimalarial drugs such as chloroquine are accumulated (Yayon et al 1984). Chloroquine is though to act by preventing the monomeric hemin from forming the inert and insoluble polymer hemozoin which is derived from digestion of hemoglobin in the acidic vacuole (Slater & Ceram 1992).…”
mentioning
confidence: 99%
“…The situation has presently worsened to such an extent that the genotype of malarial parasites, so obtained from the Central Americas where chloroquine was earlier believed to be effective, has also begun to exhibit features of resistance (Elbadry et al, 2013). It has been well-established that chloroquine, in its uncharged form, freely diffuses into the erythrocyte and subsequently into the digestive vacuole (DV).Inside the DV, chloroquine after undergoing protonation, is unable to penetrate the DV membrane back (Homewood et al, 1972;Yayon et al, 1984)). It then goes on to bind to the toxic hematin molecule and prevents the development of the non-toxic haemozoin crystal.…”
Section: Chloroquine and Quininementioning
confidence: 99%